2018
DOI: 10.1039/c8cc02179a
|View full text |Cite
|
Sign up to set email alerts
|

Corannulene: a molecular bowl of carbon with multifaceted properties and diverse applications

Abstract: Unlike typical polycyclic aromatic hydrocarbons, such as coronene, which are flat and planar, corannulene is a molecular bowl of carbon. It can be imagined as the cap region of fullerene C60 or an end of a single-walled carbon nanotube. This structural distinction manifests itself in unique properties. For example, corannulene exhibits bowl-flipping dynamics, electron accepting capability, and formation of a ball-in-socket type of interaction with C60. These varied properties allow for application of corannule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
101
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(102 citation statements)
references
References 61 publications
0
101
0
1
Order By: Relevance
“…Recently, there has been an impetus in the design and synthesis of non‐fullerene electron acceptors displaying high solubility, scalability, and ease of derivatization . Corannulene, with a recently developed kilogram‐scale synthesis, high solubility due to a lack of intermolecular π–π stacking interactions, and an adjustable structure is a suitable candidate for this purpose . Pristine corannulene, however, is not as good an electron acceptor as fullerene C 60 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been an impetus in the design and synthesis of non‐fullerene electron acceptors displaying high solubility, scalability, and ease of derivatization . Corannulene, with a recently developed kilogram‐scale synthesis, high solubility due to a lack of intermolecular π–π stacking interactions, and an adjustable structure is a suitable candidate for this purpose . Pristine corannulene, however, is not as good an electron acceptor as fullerene C 60 .…”
Section: Methodsmentioning
confidence: 99%
“…[1] Corannulene,w ith a recently developed kilogram-scale synthesis, [2] high solubility due to al ack of intermolecular p-p stacking interactions, and an adjustable structure is as uitable candidatef or this purpose. [3][4][5][6][7][8][9][10][11][12][13][14] Pristinec orannulene,h owever,i sn ot as good an electron acceptora sf ullerene C 60 .T herefore, scaffold modifications with electron-withdrawing groups have been identified as av iable route to enhancet he electron affinity of the aromatic nucleus. In this regard,B oltalina's fluorinated corannulene, [16] our bis-aryl sulfones, [27] and Lentz's bis-imides/cyano derivatives [32] produces an anodics hift of 1.23, 1.35, and 1.42 V, respectively,i nt he first reversible reductionp otential of corannulene.…”
mentioning
confidence: 99%
“…These studies have revealed the potential application of corannulene derivatives in molecular electronics, for example, as organic field‐effect transistors and as possible semiconductors . A feature article facing the very broad applications of corannulenes in materials science, including supramolecular chemistry, was recently published by Stuparu …”
Section: Introductionmentioning
confidence: 99%
“…[3] Af eature article facing the very broad applications of corannulenes in materials science, including supramolecular chemistry,w as recently published by Stuparu. [4] In the following review article, the focus will be on the synthesis and structural and electrochemical properties of corannulenes containing electron-withdrawing groups.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Theb owl-shaped geometry renders buckybowls as eries of unique properties,s uch as inherent dipole and asymmetrical assembly configuration. [7] These properties are reversed with bowl inversion. Fori nstance,t he direction of molecular dipole for buckybowl inverts with the bowl inversion, which is proposed to be potential in organic ferroelectric materials.…”
mentioning
confidence: 99%